Global Investigations of Fusobacterium nucleatum in Human Colorectal Cancer - Lee, Seul A.; Liu, Fang; Riordan, Stephen M.; Lee, Cheok S.; Zhang, Li (Frontiers in Oncology, 2019)
Colorectal cancer (CRC) is the third most prevalent cancer and second in terms of mortality (1). Emerging evidence from recent studies suggests a potential role of Fusobacterium nucleatum in the development of CRC. In this article, we review studies from different geographical regions examining the association between F. nucleatum and CRC, the detection methods and the tumorigenic mechanisms. Furthermore, we discuss the potential clinical impact of F. nucleatum in CRC and suggest future study directions.